Aggregated/agglomerated and dispersed randomly oriented wavy CNTs in electrically conductive polymer nanocomposites: Impact of dispersion quality and polymer/particle interphase - Esmail Sharifzadeh; Neda Azimi; Amir Hossein Mohammadpour (Journal of Materials Research and Technology)
This study was dedicated to investigating the effects of clusters and dispersed randomly oriented wavy carbon nanotubes (CNTs) on the electrical conductivity of polymer nanocomposites. Firstly, the percolation theory was improved to include all determinative parameters of the system such as tunneling distance, number of nanoparticles in clusters and polymer phase, thickness of the polymer/particle interphase, etc. The inevitability of nanoparticle aggregation/agglomeration was theoretically investigated based on estimating the probability of CNTs being placed in cluster domains. Accordingly, each cluster was referred to as a distinguished random structure whose electrical conductivity was designated based on Ohm's law and the electrical resistance between aggregated or agglomerated nanoparticles. The electrical conductivity of the polymer/particle interphase was defined using an improved form of scaling theory, based on the molecular characteristics of the polymer matrix. Also, the contribution of the dispersed wavy CNTs, covered by the interphase, to the electrical conductivity of the system was evaluated by designing randomly oriented dispersed equivalent nanorods, representing the actual electrical performance of nanoparticles in the matrix. The variation of the theoretical content and percolation threshold of nanoparticles was indicated based on their dispersion quality and other indicative parameters. Benchmarking the model against the derived data from the literature (error <0.24%) led to obtaining some valuable quantitative information regarding the electrical conductivity of CNT clusters, impact of the interphase on the related physical features of randomly oriented CNTs, content of aggregated/agglomerated and dispersed nanoparticles, particular impact of dispersion quality on the electrical conductivity of the nanocomposite system, etc.